Ethernet Topology Discovery without Network Assistance - Black, Richard; Donnelly, Austin; Fournet, Cédric (Proceedings of 12th IEEE International Conference on Network Protocols (ICNP'04), 2004)
This work addresses the problem of Layer 2 topology discovery. Current techniques concentrate on using SNMP to query information from Ethernet switches. In contrast, we present a technique that infers the Ethernet (Layer 2) topology without assistance from the network elements by injecting suitable probe packets from the end-systems and observing where they are delivered. We describe the algorithm, formally characterize its correctness and completeness, and present our implementation and experimental results. Performance results show that although originally aimed at the home and small office the techniques scale to much larger networks.
2004 International Conference on Network Protocols (ICNP), Berlin, Germany.